Evaluating income inequality in Malaysia: A comparative study employing Gini and Theil indices with quantile regression - Kamal, Zarul Khaliff; Abdullah, Muhammad Zakir; Zaharudin , Khairul Zharif (International Journal of Accounting, Finance and Business, 2025)
Despite decades of redistributive policy, income inequality in Malaysia remains persistent. Conventional mean-based analyses fail to capture the distributional structure of inequality, particularly the extent to which disparities arise within, rather than between, demographic groups. Drawing on data from the 2019 Household Income and Expenditure Survey (HEIS2019), this study applies an integrated empirical framework that combines Theil index decomposition with quantile regression to examine the underlying dynamics of income stratification. The results indicate that more than 95 percent of total inequality originates from within-group variation, with demographic penalties intensifying at higher income levels. Between the 25th and 75th percentiles, the gender income gap widens by 69 percent, the ethnic differential increases by 91 percent, and the education-related penalty reaches RM1,435 per month. Returns to age and occupational status also rise with income, reflecting structural advantages concentrated near the top of the distribution. These findings suggest that generalised redistributive instruments are poorly matched to the actual pattern of inequality. More effective policy responses should target high-variance segments through differentiated interventions, including expanded access to tertiary education, enforcement of wage transparency, and the formalisation of employment in low-protection sectors. Precision in policy design is essential to address inequality where it is most acute.